Isolamento do vírus rábico de morcego insetívoro Myotis nigricans Isolation of the rabies virus in a specimen of the insectiverous bat Myotis nigricans - Luzia F. A. Martorelli; Elizabeth A.C. Aguiar; Marilene F. Almeida; Miriam M.S. Silva; Eliana C. R. Novaes (Universidade de São Paulo, 1995)
Relata-se um caso de infecção natural de raiva em morcego insetívoro Myotis nigricans, no Município de Ribeirão Pires, Grande São Paulo (Brasil). O diagnóstico realizou-se através das técnicas de imunofluorescência e inoculação intracerebral em camundongos, do tecido nervoso e da musculatura da região interescapular do morcego. The following is a case study of the natural infection by the rabies virus of an insectiverous bat belonging to the species Myotis nigricans in the municipality of Ribeirão Pires, Greater S. Paulo. Diagnosis was made by means of immunofluorescence and intracerebral innoculation of mice with nervous and intrascapular muscular tissues.